Earning per share sebagai variabel intervening antara rasio keuangan terhadap harga saham pada perusahaan property dan real estate - Hidayati, Laeli; Suwaidi, Rahman Amrullah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Property and Real Estate sector has an important role in the economy. The financial ratio performance obtained is quite good, but not with the share price. The purpose of this study is to find out the effect of profitability and leverage on stock prices with EPS being the intervening variable for Property and Real Estate companies listed on the Indonesia Stock Exchange 2018-2020. The population is Property and Real Estate companies on the Indonesia Stock Exchange from 2018 to 2020 as many as 273 companies. The sample method is purposive sampling obtained as many as 150 companies in accordance with existing criteria. Analysis of the data used is path analysis. According to the results of research analysis, it is said that profitability and Earning Per Share contribute to changes in stock prices. Leverage does not contribute to changes in stock prices. Profitability contributes to changes in EPS. Leverage does not contribute to changes in Earning Per Share. Then according to the results of path analysis, it is said that Earning Per Share is able to become an intervening variable on profitability and leverage on share prices of companies in the Property and Real Estate sector.